2021
DOI: 10.3389/fevo.2020.621723
|View full text |Cite
|
Sign up to set email alerts
|

Review of Dam Effects on Native and Invasive Crayfishes Illustrates Complex Choices for Conservation Planning

Abstract: Dams are among the most prevalent and extreme alterations humans have perpetrated on fluvial systems. The dramatic physical and biological changes caused by dams have been synthesized for many aquatic faunal groups, but not for crayfishes. In addition, invasive crayfish species are an increasing threat to global biodiversity, and dams have both costs and benefits with respect to crayfish invasions. North American crayfishes have imperiled native crayfishes in Europe, largely by hosting and spreading the crayfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 158 publications
0
8
0
1
Order By: Relevance
“…This shift in fish assemblage has been supported by multiple studies that have reported extirpations, higher representation of generalists, and shifts in fish assemblages upstream of reservoirs [15][16][17][18][19][20][21]. Isolation effects and community shifts have also been documented for other aquatic species, including crayfish [22].…”
Section: Introductionmentioning
confidence: 59%
“…This shift in fish assemblage has been supported by multiple studies that have reported extirpations, higher representation of generalists, and shifts in fish assemblages upstream of reservoirs [15][16][17][18][19][20][21]. Isolation effects and community shifts have also been documented for other aquatic species, including crayfish [22].…”
Section: Introductionmentioning
confidence: 59%
“…Tertiary burrowers continuously occupy surface waters and excavate burrows within those habitats. Although some work indicates selection for tertiary burrowers within beaver ponds (Adams, 2013), as relatively dispersal limited taxa (Barnett & Adams, 2021), crayfish may be constrained in their incidence and abundance response to differences in pond ecosystem properties and beaver dam size by successional stage (Meentemeyer & Butler, 1999;Olinger et al, 2021). Thus, crayfish community structure in beaver ponds of different stages of succession may be influenced in part by burrowing strategies, species-specific dispersal limitation, and habitat suitability determined by resource availability (Ray et al, 2001;Sferra et al, 2017) and predation risk (Olinger et al, 2021;Smith & Mather, 2013) associated with ponds of different ages.…”
Section: Stream Habitat Alterations Catalysed By Beaver Dams Can Changementioning
confidence: 99%
“…NBS like barrier removals, levee setbacks, and stream restorations could thus potentially tip the scales in favor of native aquatic species assemblages. However, in cases where dams act as barriers to the spread of invasive species, as in the case of invasive sea lampreys in the Great Lakes [106] or invasive crayfish in Europe [107], dam removals could facilitate their spread, adversely impacting native biodiversity.…”
Section: Prevent and Control Non-native Species Invasionsmentioning
confidence: 99%